Realistic dosimetry for studies on biological responses to X-rays and γ-rays - Shahmohammadi Beni, Mehrdad (J Radiat Res, 2017)
A calibration coefficient R (= D(A)/D(E)) for photons was employed to characterize the photon dose in radiobiological experiments, where D(A) was the actual dose delivered to cells and D(E) was the dose recorded by an ionization chamber. R was determined using the Monte Carlo N-Particle version 5 (MCNP-5) code. Photons with (i) discrete energies, and (ii) continuous-energy distributions under different beam conditioning were considered. The four studied monoenergetic photons had energies E = 0.01, 0.1, 1 and 2 MeV. Photons with E = 0.01 MeV gave R values significantly different from unity, while those with E > 0.1 MeV gave R ≈ 1. Moreover, R decreased monotonically with increasing thickness of water medium above the cells for E = 0.01, 1 or 2 MeV due to energy loss of photons in the medium. For E = 0.1 MeV, the monotonic pattern no longer existed due to the dose delivered to the cells by electrons created through the photoelectric effect close to the medium–cell boundary. The continuous-energy distributions from the X-Rad 320 Biological Irradiator (voltage = 150 kV) were also studied under three different beam conditions: (a) F0: no filter used, (b) F1: using a 2 mm-thick Al filter, and (c) F2: using a filter made of (1.5 mm Al + 0.25 mm Cu + 0.75 mm Sn), giving mean output photon energies of 47.4, 57.3 and 102 keV, respectively. R varied from ~1.04 to ~1.28 for F0, from ~1.13 to ~1.21 for F1, and was very close to unity for F2.